minister1221
New member
- Joined
- Mar 27, 2021
- Messages
- 3
I have a section of a problem and I am unsure which concept it is referring back to on step #3.
1. f(s) = s(1-s) / (1+s)
2. f(s) = -s2 - 2s + 1 / (1+s)2
3. s2 + 2s - 1 = 0
4. (1+s)2 = 2
5. s = -1 + sqrt 2
What is happening on step #3? How is it that you set the derivative of f(s) = s(1-s) / (1+s) equal to 0 in that fashion?
1. f(s) = s(1-s) / (1+s)
2. f(s) = -s2 - 2s + 1 / (1+s)2
3. s2 + 2s - 1 = 0
4. (1+s)2 = 2
5. s = -1 + sqrt 2
What is happening on step #3? How is it that you set the derivative of f(s) = s(1-s) / (1+s) equal to 0 in that fashion?